Perceived effectiveness of Accounting Information System (AIS): a descriptive study of the Malaysian Federal Government - Sharinah Puasa; Sharifah Milda Amirul (2020)
Accounting Information System (AIS) is an integral part not only in business processes but also in government operations. While most of the governments around the world have been moving towards digitization for operational and communication purposes, AIS plays significant roles for greater operating effectiveness. Hence, it is essential to measure AIS effectiveness. Nevertheless, there exist inconsistencies when it comes to assessing AIS effectiveness due to diverse measurements. Also, the divergent in AIS effectiveness measurements is arguably due to its dynamic nature which depending upon how it is defined. However, such existing AIS measurements are not well justified. It leads to incomparability and lack of generalization. Therefore, this study revisits the existing literature to list the AIS effectiveness criteria. A quantitative method using survey questionnaire was conducted to obtain internal users’ perception towards AIS in the context of the Malaysian Federal Government. Interestingly, satisfaction scale was applied to represent the level of effectiveness highlighting the conceptual definition of effectiveness (i.e. fulfilling users’ requirements). This study emphasized that high satisfaction level indicates a highly effective system and vice versa. The result provides descriptive findings on the level of AIS effectiveness in the context of the Malaysian Federal Government. Overall, this study found a moderate level of AIS effectiveness of the Malaysian Federal Government based on the system users’ satisfaction towards six (6) criteria: Ease of Use; Processing Speed; Accurate Information; Complete Information; Relevancy of Information for the Use in making Decision; Improve Decision Making Process. The result offers evidence on the need for AIS improvement or users’ attention on the specific criteria (i.e. system processing time, the accuracy of the information in the system and relevancy of the information for the use in decision-making) that require top management’s concern. In reality, continuous improvement is crucial to sustain system effectiveness.